CRITERIA FOR DETERMINING THE PERMISSIBLE SPEED IN CURVES - Kurhan, M. B. (Science and Transport Progress, 2003)
The existing criteria of admitted speed definition of movement in curves are analysed, directions of development are specified by consideration of high-speed movement.